Explosive cyclogenesis and an atmospheric river. (27th October 2021) - Smart, David; Graham, Edward
Abstract : Integrated water vapour transport (IVT) from 1000 to 300hPa in the North Atlantic region 1200 utc 21 September 2021 obtained from a Weather Research and Forecasting (WRF) model run initialised with Global Forecast System (GFS) operational analysis data showing an 'atmospheric river' associated with an explosively deepening cyclone which produced extreme winds over Iceland.